1994
DOI: 10.1021/bk-1995-0582.ch019
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Hydroxamic Acids in the Control of Cereal Pests, Diseases, and Weeds

Abstract: Hydroxarnic acids derived from 2-hydroxy-l,4-benzoxazin-3-one are secondary metabolites present in major agricultural crops such as wheat, maize and rye. Progress in research related to their ecological role in plants is summarized, as well as to potential uses in the control of pests, diseases and weeds. Problems presently limiting the exploitation of these compounds in plant protection are discussed.In the last, few decades, the dependence on fossil-fuel-based agrochemicals such as fertilizers and pesticides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 32 publications
1
49
0
1
Order By: Relevance
“…The deterrent effect of Hx would cause a delay in the time needed to attain a first sieve element salivation (Niemeyer & Pérez, 1995;Ramírez et al, 1999). Brief cell punctures in the sieve elements may also occur (Tjallingii & Hogen Esch, 1993) and can contribute in such a delay.…”
Section: Resultsmentioning
confidence: 99%
“…The deterrent effect of Hx would cause a delay in the time needed to attain a first sieve element salivation (Niemeyer & Pérez, 1995;Ramírez et al, 1999). Brief cell punctures in the sieve elements may also occur (Tjallingii & Hogen Esch, 1993) and can contribute in such a delay.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, in vitro supplied DIMBOA has been demonstrated to affect a broad spectrum of herbivorous insects and microbes, including aphids (Cambier et al, 2001) and S. turcica (Rostás, 2007). Other studies revealed negative correlations between endogenous BX concentrations and aphid performance in populations of cereal varieties (Argandoñ a et al, 1980;Leszczynski and Dixon, 1990;Niemeyer and Perez, 1994). In this study, we have investigated the defense function of BXs further, by comparing resistance phenotypes of wildtype and bx1 maize lines in the background of the igl mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxamic acids (Hx) are defensive metabolites typical of Gramineae (Niemeyer and Perez, 1995). Hx are induced in wheat by aphid feeding, and this induction is affected by plant genotype (Niemeyer et al, 1989), aphid genotype , and environmental conditions .…”
Section: Introductionmentioning
confidence: 99%